Etno-Jurnalisme pada Produksi Film Dokumenter Jakarta Unfair - Octi Sundari (ULTIMA Comm, 2018)
ABSTRACTJournalism works cannot be separated from its inherent values. The values, such as objectivism, speed, and balance, have been the journalist professional norms. However, some journalism values hamper the works and might produce on shallow reporting. In an attempt to address the problem, journalism adopt etnographic approach in social science, or known as ethno-journalism. Ethno-journalism is important in producing holistic and indepth report amid the focus of journalism on speed. This research aims to analyse the practice of ethno-journalism in the production of Jakarta Unfair documentary. This qualitative research uses explanatory analysis from case study model of Robert E. Stake. The result mainly show the incomplete ethno-journalism practice in the production of Jakarta Unfair.Keywords: ethnography, documentary, Jakarta Unfair, Journalism